Biodiversitas Ikan Karang Famili Pomacentridae Di Perairan Kota Jayapura, Provinsi Papua - Baigo Hamuna; Lisiard Dimara; Yunus Pajanjan Paulangan (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2020)
This study aims to determine the diversity, distribution, and ecological index of coral fish from the Pomacentridae family in the coral reef ecosystem of Jayapura City. Reef fish observations were carried out in April 2020 at seven study sites. The fish observation was carried out at a depth of 3 to 5 m using the Underwater Visual Census method. Ecological indices were determined using PAST software (PAleontological Statistics) version 4.01, while the similarity index between study sites was determined using PRIMER 7 software. The results showed that the number of coral fish species of Pomacentridae family was 35 species with a total of 346 individual fish. The species distribution was very diverse and no fish species were found at all study sites. The diversity index ranges from 0.572 to 2.215 (low to moderate category), the evenness index ranges from 0.431 to 0.886 (medium to high category), and the dominance index ranges from 0.145 to 0.616 (low to moderate category). The diversity index at Base-G, Pulau Kayupulo, and Lampu Merah sites shows the fish community is classified as medium diversity with high evenness. There are similarities between study sites, where the species N. filamentosus contributed to the formation of group A (Base-G and Argapura 1 sites), while P. moluccensis, C. margaritifer, and P. taeniometopon species contributed to the formation of group B (Argapura 2, Pulau Kosong 1, Pulau Kosong 2, Pulau Kayupulo, and Lampu Merah sites).Keywords: Coral reef; Reef fish; Ecological index; Community structure; Similarity index